(untitled) (Sebha University Conference Proceedings, 2024)
Water injection has proven to be one of the most successful, efficient and cost-effective reservoir management strategies. By reinjecting treated and filtered water into tanks, this approach can help maintain tank pressure, increase hydrocarbon production, and reduce environmental impact. The goal of this project is to create a water injection model using Eclipse tank simulation software to better understand water injection methods to maintain tank pressure. A basic reservoir model is utilized in this investigation. The simulation was performed about 52 years using ECLIPSE Reservoir simulator. In all cases, result shows that oil production with water injection is higher compared with the base case. With this, it would be preferred to apply waterflooding for oil recovery in depleted reservoirs to the use of primary methods. It is also observed that water breakthrough is earlier and water production increases gently with water injection rates. Sensitivity on the injection rate using the 3D model showed that the injection rate has impact on the process. The pressure increases with high injection water rate in all cases. Despite higher reservoir pressure and early in water breakthrough, water flooding accounts for less oil recovery due to rapid water production. Generally, based on the results and discussions, it can be concluded that the water injection option can be used to increase the reservoir pressure to a good extent.